Towards a framework for developing and assessing pre-service EFL teachers’ classroom English proficiency - Nikolovska, Anžela (Glottodidactica, 2025)
Although EFL teachers’ classroom language proficiency constitutes a core component of teacher expertise and a crucial dimension of effective teaching, it still remains an elusive concept, as it is too complex to be fully conceptualised. The article elaborates on the procedure for designing a learning-oriented English-for-teaching purposes assessment (ETPA) implemented at a North Macedonian university to enhance and assess pre-service English teachers’ classroom English proficiency through teacher, peer and self-assessment. First, it provides a brief review of the relevant studies on EFL teachers’ language proficiency as English for specific purposes (ESP) and the literature on learning-oriented assessment (LOA). Next, it describes the process of operationalising the instructional, regulative and dialogic function of teacher talk in the criteria of accuracy, fluency, interaction, stimulating the development of ideas and addressing audiences customised from the Common European Framework of Reference for Languages (CEFR). The results of a survey of students’ perceptions of the assessment tool revealed that they were mostly positive, with few suggestions for improvement. Finally, conclusions are drawn regarding the potential of the proposed framework to inform future research despite its limitations.